2018
DOI: 10.1016/j.jjcc.2018.05.020
|View full text |Cite
|
Sign up to set email alerts
|

A versatile transapical device for aortic valvular disease: One-year outcomes of a multicenter study on the J-Valve system

Abstract: Our study provides further evidence on the safety and efficacy of the J-Valve in high-risk patients with AS or AR for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
(21 reference statements)
1
17
0
1
Order By: Relevance
“…A total of 69 patients with severe symptomatic AS who were treated with J-Valve (JieCheng Medical Technologies, Suzhou, China) were included between March 2014 and July 2017. Of these patients, 64 participated in J-Valve China clinical trial at three cardiac centers (Fuwai Hospital, West China Hospital, and Zhongshan Hospital) 4,12) to get official approval from China Food and Drug Administration. From December 2012 to April 2016, 63 patients treated with Venus-A THV (Venus MedTech, Hangzhou, China) were also enrolled in this study.…”
Section: Patient Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 69 patients with severe symptomatic AS who were treated with J-Valve (JieCheng Medical Technologies, Suzhou, China) were included between March 2014 and July 2017. Of these patients, 64 participated in J-Valve China clinical trial at three cardiac centers (Fuwai Hospital, West China Hospital, and Zhongshan Hospital) 4,12) to get official approval from China Food and Drug Administration. From December 2012 to April 2016, 63 patients treated with Venus-A THV (Venus MedTech, Hangzhou, China) were also enrolled in this study.…”
Section: Patient Selectionmentioning
confidence: 99%
“…The feasibility and convincing short-term outcome of J-Valve was reported in our previous study. 4,12) However, compared with the reported results of other THVs, 13,14) it was observed that the patients treated with J-Valve showed a relatively higher transaortic pressure gradient. We speculated the phenomenon attributing to the frame design of this prosthesis.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…12) In addition, the feasibility of TAVI for patients with PAR was proven in several second-generation THV, including Evolut-R, 18) SAPIEN 3, 8) ACURATE neo, 9) Direct Flow Medical, 10) Lotus 11) et al The 1-year outcome of TAVI using a second-generation THV (J-Valve and Jenavalve) for PAR has been reported, and it presented a satisfactory outcome. 4,5,7) However, the long-term durability and efficiency of these devices were not demonstrated. Our study first reported the long-term follow-up of TAVI using J-Valve for PAR, and the dependable durability and Continuous variables were performed as mean ± standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of transcatheter heart valve (THV) devices and the technique of TAVI procedure, the second-generation THV has revolutionized the interventional treatment for PAR. 4,5) There are multiple reports presenting the feasibility of transcatheter approach for the treatment of PAR, 4,[6][7][8][9][10][11] and second-generation devices associated with an excellent procedural success rate and favorable perioperative outcomes compared with first-generation THV. In second-generation devices, the advantage is more pronounced on the "on-label" THVs (J-Valve and JenaValve) than "off-label" THVs.…”
Section: Introductionmentioning
confidence: 99%